The Gambia : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report, 2011)
The Poverty Reduction Strategy Paper (PRSP) describes The Gambia's macroeconomic, structural, and social policies in support of growth and poverty reduction, external financing needs, and major sources of financing. Since PRSP I had experienced some setbacks during its implementation, PRSP II has been formulated with revised strategies to achieve Vision 2020 and the Millennium Development Goals (MDGs) of reducing poverty globally. Based on a detailed analysis, the authorities provided some specific recommendations for the long-term sustainability of the program in terms of priorities and operational modalities.